Fortran 2018 with Parallel Programming. - Ray, Subrata ([Place of publication not identified] : Chapman and Hall/CRC, 2019)
The programming language Fortran dates back to 1957 when a team of IBM engineers released the first Fortran Compiler. During the past 60 years, the language had been revised and updated several times to incorporate more features to enable writing clean and structured computer programs. The present version is Fortran 2018. Since the dawn of the computer era, there had been a constant demand for a "larger" and "faster" machine. To increase the speed there are three hurdles. The density of the active components on a VLSI chip cannot be increased indefinitely and with the increase of the density heat dissipation becomes a major problem. Finally, the speed of any signal cannot exceed the velocity of the light. However, by using several inexpensive processors in parallel coupled with specialized software and hardware, programmers can achieve computing speed similar to a supercomputer. This book can be used to learn the modern Fortran from the beginning and the technique of developing parallel programs using Fortran. It is for anyone who wants to learn Fortran. Knowledge beyond high school mathematics is not required. There is not another book on the market yet which deals with Fortran 2018 as well as parallel programming. FEATURES Descriptions of majority of Fortran 2018 instructions Numerical Model String with Variable Length IEEE Arithmetic and Exceptions Dynamic Memory Management Pointers Bit handling C-Fortran Interoperability Object Oriented Programming Parallel Programming using Coarray Parallel Programming using OpenMP Parallel Programming using Message Passing Interface (MPI) THE AUTHOR Dr Subrata Ray, is a retired Professor, Indian Association for the Cultivation of Science, Kolkata.
Preliminaries. Arithmetic, Relational, Logical Operators and Expressions. Branch and Loop Statements. Handling of Characters. Precision and Range. Array and Array Handling Intrinsics. User Defined Data Type. Format Statement. Auxiliary Storage. Numerical Model. Library Functions. Subprograms. String with Variable Length. IEEE Floating Point Arithmetic and Exception. Dynamic Memory Management. Pointer. Bit Handling. C-Fortran Interoperability. Object Oriented Programming. Parallel Programming Using Coarray. Parallel Programming Using OpenMP. Parallel Programming Using Message Passing Interface (MPI).Appendix A. Appendix B. Appendix C. Appendix D. Appendix E. Appendix F. Appendix G. Appendix H. Appendix I. References. Index.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Programming Languages / General; COMPUTERS / Computer Engineering; FORTRAN (Computer program language); Parallel programming (Computer science)